Balancing Redox Reactions: Acidic Solutions Video Lessons

Concept: Balancing Redox Reactions: Acidic Solutions

# Problem: Balance the following redox reactions occurring in acidic aqueous solution.Zn(s)+Sn2+(aq)→Zn2+(aq)+Sn(s)Express your answer as a chemical equation. Identify all of the phases in your answer.

###### FREE Expert Solution

Balance the redox reaction under acidic conditions:

Zn(s) + Sn2+(aq) → Zn2+(aq) + Sn(s)

*Before balancing the redox reaction:

ignore H+, OH-, and H2O in the starting reaction

Step 1: Separate the whole reaction into two half-reactions

Zn(s) → Zn2+(aq)                                                               Sn2+(aq) → Sn (s)

Step 2: Balance the non-hydrogen and non-oxygen elements first

Zn(s) → Zn2+(aq)                                                              Sn2+(aq) → Sn (s)

(Znbalanced)                                               (Snbalanced)

No need to balance O or H (no O, H)

Step 3: Balance the charges: add electrons to the more positive side (or less negative side)

▪ For species that are neutral: oxidation state = 0

▪ For ions (or species with charges): oxidation state = charge of the ion

▪ The reactant side and the product side should have an equal overall charge (after adding electrons)

Zn(s) → Zn2+(aq)                                                Sn2+(aq) → Sn (s)

Reactants                            Products                               Reactants                            Products

Zn = 0                                    Zn2+ = +2                              Sn2+ = +2                                   Sn = 0

+2 e- = (-1) x 2 = -2

-----------------------                 ------------------------                     +2 e- = (-1) x 2 = -2

overall = 0                             overall = 0                             -------------------------------              ----------------

overall = 0                          overall = 0

95% (455 ratings)
###### Problem Details

Balance the following redox reactions occurring in acidic aqueous solution.

Zn(s)+Sn2+(aq)→Zn2+(aq)+Sn(s)